Problems in micro financing of Bangladesh: a study on Grameen Bank - Md. Ferdausur, Rahman (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my